THE POTENTIAL OF SUSTAINABLE LIVELIHOOD-BASED TOURISM IN KUTA JUNGAK TOURISM VILLAGE, PAKPAK BHARAT DISTRICT - Nova Bernedeta Sitorus; Liyushiana Liyushiana; Deafani Clara Sinaga (LPPM Institut Pendidikan Nusantara Global, 2023)
To identify the topic of sustainable livelihood, the author tried to make the Kuta Jungak Tourism Village in Pakpak Bharat District, Siempat Rube District and founded in 2005The development of the Kuta Jungak Tourism Village has received support from the local community, although it has yet to attract many visits. This study aimed to identify the potential for sustainable livelihood-based tourism for the people of Kuta Jungak Tourism Village. This study aimed to identify the potential for sustainable livelihood-based tourism in the Kuta Jungak Tourism Village, Pakpak Bharat Regency. This study used qualitative research methods. The informants in this study were the managers of the Kuta Jungak Tourism Village and the village community. Kuta Jungak Tourism Village, when viewed from the tourism potential according to the tourism component 4A, has the potential to make this village a pilot tourism village. However, it continues, and this village has many tasks in developing a tourist village. Furthermore, the concept of sustainable livelihood can be used as a reference in developing the Kuta Jungak Tourism Village with its five indicators. After reviewing it, it was found that for each indicator of sustainable livelihood, all indicators had yet to be implemented in the Kuta Jungak Tourism Village. Existing potential must be developed to attract tourist visits and provide positive benefits for the welfare of rural communities and assist the government in achieving village development indicators.